Cocaine enhances HIV‐1 gp120‐induced lymphatic endothelial dysfunction in the lung. Issue 8 (26th August 2015) - Zhang, Xuefeng; Jiang, Susan; Yu, Jinlong; Kuzontkoski, Paula M.; Groopman, Jerome E.
Abstract Pulmonary complications are common in both AIDS patients and cocaine users. We addressed the cellular and molecular mechanisms by which HIV and cocaine may partner to induce their deleterious effects. Using primary lung lymphatic endothelial cells (L‐LECs), we examined how cocaine and HIV‐1 gp120, alone and together, modulate signaling and functional properties of L‐LECs. We found that brief cocaine exposure activated paxillin and induced cytoskeletal rearrangement, while sustained exposure increased fibronectin (FN) expression, decreased Robo4 expression, and enhanced the permeability of L‐LEC monolayers. Moreover, incubating L‐LECs with both cocaine and HIV‐1 gp120 exacerbated hyperpermeability, significantly enhanced apoptosis, and further impaired in vitro wound healing as compared with cocaine alone. Our studies also suggested that the sigma‐1 receptor (Sigma‐1R) and the dopamine‐4 receptor (D4R) are involved in cocaine‐induced pathology in L‐LECs. Seeking clinical correlation, we found that FN levels in sera and lung tissue of HIV+ donors were significantly elevated as compared to HIV− donors. Our in vitro data demonstrate that cocaine and HIV‐1 gp120 induce dysfunction and damage of lung lymphatics, and suggest that cocaine use may exacerbate pulmonary edema and fibrosis associated with HIV infection. Continued exploration of the interplay between cocaine and HIV should assist the design of therapeutics to ameliorate HIV‐induced pulmonary disorders within the drug using population.